Expert Opinion Process: Applications in Education - Bayona-Ore, Luz (2018)
Expert opinion is a technique used in different areas of scientific research, which, in some way, guarantees its social and methodological validity. This method is also used as an instrument to make long-term predictions, with different types of solutions to obtain a concise answer that is achieved with the help of experts who exchange information, cultures and experiences to provide solutions to the relevant and timely problems that may arise. The purpose of this article is to review the quality literature regarding experts' opinion of different applications. This research resulted in an extensive relationship with the topics of technology, technology foresight, and especially education.